'Implementing a broad quality of life tool for determining care wishes and needs of older adults living at home. Issue 4 (2nd October 2021) - Van Loon, M. S.; Widdershoven, G.; Van Leeuwen, K.; Bosmans, J.; Metselaar, S.; Ostelo, R.
ABSTRACT: The aim was to investigate the views of stakeholders on the practical relevance of a broad quality of life (QoL) outcome tool for care in older adults: the Extended Quality of Life Tool (EQLT). We conducted individual interviews and focus groups with a variety of stakeholders involved in the care for older adults which were analyzed using a framework analysis. Stakeholders considered relevant: focus on the client perspective; perspective on QoL broader than health; the possibility to take diversity into account; and the possibility to determine a minimum level of QoL. Three facilitators for implementation of the tool were mentioned as well as four barriers. The EQLT can support conversations with clients about their needs and wishes, thus enabling decisions about care services based on a broad set of domains of QoL. Implementation of the tool should take into account the facilitators and barriers identified in the current study.